Electronic Word of Mouth, Brand Awareness, Brand Image and Customer Satisfaction - I Gusti Agung Ngurah Rai Semadi; Ni Nyoman Sunariani (Jurnal Manajemen dan Bisnis, 2016)
The object in this research is Electronic Word of Mouth, Brand Awareness,Brand Image and Customer Satisfaction. This research aims find out the relationship andinfluence of variable Electronic word of mouth, brand awareness, and brand image informing or creating Customer Satisfaction.From this research, four the hypothesis that test is done to 107 respondents who waschosen by judgement sampling technique is conducted sampling technique based onthe characteristics set is minimal stayed previously at Legian Village Hotel. Tabulation ofthe data processed by the program AMOS v22. With the results of studies showing the cutof value and goodness of fit looks four criteria are met eight criteria used. Relative criteriaare met including Chi-square (?2 / df), Probability, TLI, and CFI and the marginal is GFI.Thus it was more than two criteria that qualify, then the model can already be said to begood.It is expected that this research can connect the implications theoretical and theimplications for companies with the result that overall has been described in this chapterclosing sub-section conclusion.Keywords: Electronic Word of Mouth, Brand Awareness, Brand Image, CustomerSatisfaction.